Interferences in the yeast estrogen screen (YES) assay for evaluation of estrogenicity in environmental samples, chemical mixtures, and individual substances. (April 2023) - Gomes, Giselle; Argolo, Allan dos Santos; Felix, Louise da Cruz; Bila, Daniele Maia
Abstract: The Yeast Estrogen Screen (YES) has a specific mechanism of action that allows for the analysis of estrogenic EDC at low concentrations, and it has been broadly used to estimate the estrogenic potential of environmental samples. However, the experimental parameters of this assay still demand an investigation, such as cell density, incubation time, wavelength on the experimental outcome, cytotoxicity, and estrogenic activity adsorbed on suspended solids. We studied these interferences and applied the assay to single substances, mixtures, and environmental matrices from different sources. The increase in cell density amplifies the assay sensitivity only to a limited extent, while the reduction in incubation time decreased assay sensitivity - although it was not significant for surface water, no differences were observed between estradiol-equivalents derived of 48 h and 72 h measurements. The particulate phase was of utmost importance for the total estrogenic activity of the landfill leachate and surface water. Surface waters, landfill leachates and sediments also showed antiestrogenic activity and the integration of both estrogenic and antiestrogenic endpoints provided deeper insights into the potential risk associated with EDC. This study elucidated experimental interferences that may arise during the implementation and use of this assay, bringing more understanding to experimental parameters during the application of the assay for estrogenicity screening. Graphical abstract: Unlabelled Image Highlights: Wavelength selection, cell density, and incubation time interfere with sensibility. Increasing cell density increased the assay sensitivity only to a limited extent. Reducing the incubation time decreased the sensitivity of the assay. Cell density control ensured uniform EC50 distribution as shown by the control charts. No differences were observed between E2-EQ. 48/72 h measurements for surface waters.